African’s Information and Communications Technology (ICT), Innovations and Economic Growth- Towards region integration: Empirical Evidence of Dynamic GMM Panel Data Approach. - Khater, Ahmed Mohammed (Archives of Business Research, 2022)
Current literature on economic growth and development uniformly affirms the consensus that Information and Communication Technology ICTs (here defined as the composite index using 11 indicators as developed by (ITU)) is indispensable for economic growth and enhancing a wide range of development indices. It is common knowledge today that Information and Communication Technology (ICT) -whether embodied in human skills, capital goods, practices and organizations—are the key drivers of economic growth and sustainable development of nations and regions. The integration, growth and competitiveness of the economies of the East African Community (EAC) depend on Information and Communication Technology (ICT) and innovation. This paper examines the impact of Information and Communication Technology (ICT) use on economic growth using the Generalized Method of Moments (GMM) estimator within the framework of a dynamic panel data approach and applies it to five East Africa community Countries (EAC) countries over the period 2000 to 2018.The results indicate that there is a positive relationship between real GDP Growth and ICT Development index (as a composite index measured by the number of indicators which are, ICT readiness reflecting the level of network infrastructure and access to ICTs, ICT intensity reflecting the level of use of ICT in the society and ICT (skills) impact reflecting the result/outcome of efficient and effective ICT user). This implies that if these countries seek to enhance their economic growth, they need to implement specific policies that facilitate ICT development. The ﬁve Partner countries of the EAC should make closer cooperation strategies, systematic and signiﬁcant regional integration arrangements in the generate and application of new knowledge and technological innovations, their ambitions to grow their economies, achieve Millennium Development Goals (MDGs) targets, deepen economic and political integration and attain sustainable development.